Acceptability of Vaccines Against Preventable Infections Including Coronavirus Disease 2019 Among Patients With Rheumatic Disease. Issue 1 (6th October 2021) - Tedeschi, Sara K.; Ellrodt, Jack; Stratton, Jacklyn; Santacroce, Leah; Chandler, Paulette D.; Gravallese, Ellen M.; Solomon, Daniel H.
Abstract : Objective: Vaccination against preventable infections is widely recommended for patients with systemic rheumatic disease. The coronavirus disease 2019 (COVID‐19) pandemic has highlighted variability in attitudes toward vaccination, particularly with the use of novel vaccine platforms. We studied attitudes toward vaccination against COVID‐19 and other preventable infections among patients with systemic rheumatic disease and compared these against the general population. Methods: We surveyed patients treated at Brigham and Women's Hospital for systemic rheumatic disease using a secure web‐based survey or paper survey in English or Spanish, from December 2020 to April 2021. We included survey questions used in the nationwide Harris Poll (October 2020 and February 2021), allowing the comparison of responses with those from the general population. Response frequencies were estimated and compared using descriptive statistics. Results: Of 243 participants (25% response rate), the mean age was 56 years, 82% were women, and 33% were nonwhite. Rheumatoid arthritis (50%) and systemic lupus erythematosus (28%) were the most common diagnoses. Thirty percent had been hospitalized previously for any infection. Seventy‐six percent worried a lot or somewhat about contracting COVID‐19. Attitudes toward vaccination were very favorable, with 92% having received a flu shot in the past year and 84% desiring a COVID‐19 vaccine as soon as possible compared with 30% to 40% of Harris Poll respondents ( P < 0.001). Physician recommendation to receive a vaccine and desire to avoid infection were the most common reasons for desiring vaccinations. Conclusion: Vaccine acceptability, including toward COVID‐19 vaccines, was high among this population of patients with systemic rheumatic disease seen at an academic medical center cohort. Physician recommendation is a key factor for vaccine uptake.